2014
DOI: 10.3201/eid2012.131820
|View full text |Cite
|
Sign up to set email alerts
|

Residual Infestation and Recolonization during UrbanTriatoma infestansBug Control Campaign, Peru1

Abstract: Recolonization from untreated households is a serious threat to long-term vector control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…Based on unpublished data, we know that in these localities (treated prior to 2009) campaign participation rates were consistently above 80% (Barbu et al, 2014; Levy et al, 2006). The campaign has since progressed to more urban districts where infection prevalence is estimated at 2.28% (Hunter et al, 2012).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on unpublished data, we know that in these localities (treated prior to 2009) campaign participation rates were consistently above 80% (Barbu et al, 2014; Levy et al, 2006). The campaign has since progressed to more urban districts where infection prevalence is estimated at 2.28% (Hunter et al, 2012).…”
Section: Methodsmentioning
confidence: 97%
“…However, IRS requires high levels of household participation to be effective and cost-effective. A suboptimal level of participation will permit vector populations to rebound from untreated households, and eventually recolonise already-treated communities (Barbu et al, 2014). Therefore, understanding the household’s decision to participate in IRS campaigns is crucial to the success of the campaign.…”
Section: Introductionmentioning
confidence: 99%
“…The equation for V predicts high sensitivity to adult survival and many studies demonstrate how this conclusion is highly dependent on a suite of assumptions that may be unrealistic in real field settings where mortality rates and population mixing are not constant, vector-host interactions are environmentally dependent and vector-pathogen interactions vary with genetic structure (Bellan 2010;Smith et al 2014). Perhaps less well recognized is the importance of the socio-economic environment of modern cities that can affect entomological parameters and efficacy of vector control (Bartlett-Healy et al 2011;Fonseca et al 2013;Barbu et al 2014;Buttenheim et al 2014). Social factors interact with the biophysical environment to create a complex and often hard to predict, socio-ecological context within which vector-borne diseases circulate.…”
Section: Discussionmentioning
confidence: 99%
“…Household insecticide use and uptake of insecticide campaigns in Peru has been studied predominantly in response to serious health threats from vector-borne disease (1-3, 5, 6, 10). In Arequipa and surrounding areas where the current study was conducted, insecticide research efforts have focused particularly on addressing triatomine, or "kissing bug," populations in response to Chagas disease (1,(11)(12)(13)(14). One residential insecticide spray campaign in peri-urban Arequipa in 2012 reached only 66% of homes, and a study found that primary reported barriers included practical concerns such as spray times coinciding with work obligations and difficulties preparing the home, as well as concerns about the health impacts of insecticides and a perception that the campaign was not necessary (1).…”
Section: Introductionmentioning
confidence: 99%